Detection of MSH2 Gene Methylation in Extramammary Paget's Disease by Methylation-Sensitive High-Resolution Melting Analysis. (1st November 2021) - Dong, Liu; Zhu, Yingfeng; Wu, Liting; Zhang, Qiaoan; Xu, Feng; Zhang, Xinju; Xu, Xiao; Tang, Yiting; Ren, Guoqiang; Kang, Zhihua; Guan, Ming
Abstract : Background . Extramammary Paget's disease (EMPD) is a rare skin tumor. Hypermethylation in the MSH 2 promoter resulting in the downregulation of its protein expression shows a high detection rate in EMPD tumor tissue, which indicates that the methylation of MSH 2 may play an important role in the pathogenesis of EMPD. Objective . This study aims to establish a rapid analysis strategy based on the methylation-sensitive high-resolution melting curve (MS-HRM) to detect the methylation level of the MSH 2 promoter. Methods . With the use of universal methylated human DNA products, we established the MS-HRM standard curve to quantitatively detect the methylation level of the MSH 2 promoter. Then, all 57 EMPD tumor DNA samples were analyzed. Pyrosequencing assay was also carried out to test the accuracy and efficacy of MS-HRM. Besides, a total of 54 human normal and other cancerous tissues were included in this study to test the reliability and versatility of the MS-HRM standard curve. Results . In this study, by using the established MS-HRM, we found that 96.5% (55/57) EMPD tumor samples had varying methylation levels in the MSH 2 promoter ranging from 0% to 30%. Then, the methylation data were compared to the results obtained from pyrosequencing, which showed a high correlation between these two techniques by Pearson's correlation ( r  = 0.9425) and Bland–Altman plots (mean difference = −0.1069) indicating that the methylation levels analyzed by MS-HRM were consistent with DNA pyrosequencing. Furthermore, in 23 normal and 31 other cancerous tissue samples, there were two colorectal cancer (CRC) tissues that tested MSH 2 methylation positive (1% and 5%) which confirmed that our established MS-HRM can be widely applied to various types of samples. Conclusion . MS-HRM standard curve can be used for the detection of the methylation level of MSH 2 in EMPD tumor samples and other cancerous tissues potentially, which presents a promising candidate as a quantitative assay to analyze MSH 2 promoter methylation in routine pathological procedure.